Antibacterial activity of medicinal plants against uropathogenic Escherichia coli - Razan Salman Marouf; Joseph Arsene M. Mbarga; Andrey V Ermolaev; Irina V Podoprigora; Irina P Smirnova; Natalia V Yashina; Anna V Zhigunova; Aliya V Martynenkova (Wolters Kluwer Medknow Publications, 2022)
Urinary tract infections (UTIs) are one of the most common bacterial infections with uropathogenic Escherichia coli (UPEC) being the most prevalent causative agent in both complicated and uncomplicated UTIs. Antibiotic resistance among UPEC has been already demonstrated against a wide variety of antibiotics and the situation is continuing to deteriorate increasing the rate of recurrence and the difficulty of treatment and prophylaxis. Recently, a big attention has been paid to non-antibiotic approaches as an alternative to conventional antibiotics. Among many strategies, phytotherapy has gained a special attention worldwide. Herbal remedies have been used in traditional medicine since ancient times and they are well known for their effectiveness in treating many health conditions including UTIs. Researches are conducted continuously to validate the use of many medicinal plants against UPEC, investigate their mechanisms of action, and determine their active constituents. Our extensive review of the recent literature revealed that many phytochemicals are shown to target and inhibit a wide variety of bioprocesses in UPEC, such as adhesion, motility, biofilm formation, and quorum sensing. Such natural approaches are very promising in confronting the antibiotic resistance of UPEC and can be further used to develop plant-based strategies and pharmaceutical products to treat and prevent UTIs caused by UPEC.